BIOPESTISIDA DAUN SIRSAK DAN TEMBAKAU SEBAGAI PENANGGULANGAN HAMA ULAT YANG RAMAH LINGKUNGAN - Jupri, Ahmad; Diva, Ni Putu Natasa; Cahya, Maeliandri Aulia; Fadli, Fadli; Rozi, Tapaul; Prasedya, Eka Sunarwidi; Ahyadi, Hilman (Jurnal Pepadu, 2024)
Vegetables are important in consumption as well as economic producers for the people of Indonesia. This is inseparable from the life of the Paok Pampang community, most of whose residents work as field and vegetable farmers. Fields planted with vegetables are very vulnerable to pests, especially caterpillar pests. The efforts made by farmers in overcoming caterpillar pests are to rely on the use of synthetic pesticides which unwittingly have a negative impact on health and the environment. In addition, the use of synthetic pesticides is quite costly for farming. Public awareness to avoid and reduce the use of synthetic pesticides and switch alternatives to organic pesticides is needed. Biopesticides made from organic materials including soursop leaves and tobacco are certainly environmentally friendly and can reduce the cost of farming. However, the lack of public knowledge about pesticides is a problem in pest management in the agricultural sector. Therefore, with the socialization and counseling activities program on biopesticides can help increase public awareness and understanding of the use of environmentally friendly biopesticides. It is hoped that the community, especially farmers, will be able to leave agricultural materials that can damage health and the environment in the sense of reducing or even abandoning the use of synthetic pesticides and always using biopesticides from organic materials. It is even expected that farmers will be able to produce their own biopesticides for the welfare of farmers in Paok pampang village.